A genetic algorithm for the detection of new cis-regulatory modules in sets of coregulated genes - Aerts, Stein; Van Loo, Peter; Moreau, Yves; De Moor, Bart (Bioinformatics, 2004)
The implementation of a genetic algorithm is described that provides a fast method of searching for the optimal combination of transcription factor binding sites in a set of regulatory sequences. Availability: The algorithm can be used transparently as a web service from within the Toucan software. Toucan can be accessed at http://www.esat.kuleuven.ac.be/~saerts/software/toucan.php. A standalone version of the software is available upon request.